Chronic hypoxia increases arterial blood pressure and reduces adenosine and ATP induced vasodilatation in skeletal muscle in healthy humans. (30th June 2014) - Calbet, J. A. L.; Boushel, R.; Robach, P.; Hellsten, Y.; Saltin, B.; Lundby, C.
Abstract Aims To determine the role played by adenosine, ATP and chemoreflex activation on the regulation of vascular conductance in chronic hypoxia. Methods The vascular conductance response to low and high doses of adenosine and ATP was assessed in ten healthy men. Vasodilators were infused into the femoral artery at sea level and then after 8–12 days of residence at 4559 m above sea level. At sea level, the infusions were carried out while the subjects breathed room air, acute hypoxia (FIO2 = 0.11) and hyperoxia (FIO2 = 1); and at altitude (FIO2 = 0.21 and 1). Skeletal muscle P2Y2 receptor protein expression was determined in muscle biopsies after 4 weeks at 3454 m by Western blot. Results At altitude, mean arterial blood pressure was 13% higher (91 ± 2 vs. 102 ± 3 mmHg, P < 0.05) than at sea level and was unaltered by hyperoxic breathing. Baseline leg vascular conductance was 25% lower at altitude than at sea level (P < 0.05). At altitude, the high doses of adenosine and ATP reduced mean arterial blood pressure by 9–12%, independently of FIO2. The change in vascular conductance in response to ATP was lower at altitude than at sea level by 24 and 38%, during the low and high ATP doses respectively (P < 0.05), and by 22% during the infusion with high adenosine doses. Hyperoxic breathing did not modify the response to vasodilators at sea level or at altitude. P2Y2 receptor expression remained unchanged with altitude residence. Conclusions Short‐term residence at altitude increases arterial blood pressure and reduces the vasodilatory responses to adenosine and ATP.